Governing by Network: The New Shape of the Public Sector - Goldsmith, Stephen; Eggers, William D. (Rowman & Littlefield Publishers, 2005)
A fundamental, but mostly hidden, transformation is happening in the way public services are being delivered, and in the way local and national governments fulfill their policy goals. Government executives are redefining their core responsibilities away from managing workers and providing services directly to orchestrating networks of public, private, and nonprofit organizations to deliver the services that government once did itself. Authors Stephen Goldsmith and William D. Eggers call this new model “governing by network” and maintain that the new approach is a dramatically different type of endeavor that simply managing divisions of employees. Like any changes of such magnitude, it poses major challenges for those in charge. Faced by a web of relationships and partnerships that increasingly make up modern governance, public managers must grapple with skill-set issues (managing a contract to capture value); technology issues (incompatible information systems); communications issues (one partner in the network, for example, might possess more information than another); and cultural issues (how interplay among varied public, private, and nonprofit sector cultures can create unproductive dissonance). Governing by Network examines for the first time how managers on both sides of the aisle, public and private, are coping with the changes. Drawing from dozens of case studies, as well as established best practices, the authors tell us what works and what doesn’t. Here is a clear roadmap for actually governing the networked state for elected officials, business executives, and the broader public.